TEKNIK PEMELIHARAAN LARVA UDANG VANNAMEI (Litopenaeus Vannamei) DI HATCHERY PT. DELTA WINDU PURNAMA KABUPATEN SITUBONDO PROVINSI JAWA TIMUR - nabilah, nathania nurmala; Halim, Atika Marisa; Suprakto, Bambang (Jurnal Perikanan Pantura (JPP), 2025)
Vannamei shrimp cultivation in Indonesia has begun in East Java. Farmers in East Java cultivate vannamei shrimp, in fact 90% of farmers have replaced the tiger prawns they cultivate with vannamei shrimp. With the increase in vannamei shrimp cultivation, it is necessary to provide continuous and quality fry, so it is hoped that it will be able to increase the productivity of vannamei shrimp. The purpose of this writing is to determine techniques for rearing vannamei shrimp larvae (Litopenaeus Vannamei) at PT. Delta Windu Purnama Situbondo, East Java. The methods used in rearing vannamei shrimp larvae start from preparing rearing tanks, preparing equipment, installing aeration, fumigation of rearing rooms, preparing rearing water, stocking naupli, managing feed, managing water quality and harvesting and packaging the fry. The results obtained were that the number of larval populations produced at the end of the rearing period in tank B1 was 2,000,000 with a survival rate of 80% and in tank B5 was 2,370,000 with a survival rate of 94.8%. The population number and survival rate of vannamei shrimp larvae will decrease along with the change of larval stage which is influenced by environmental conditions and food availability. The water quality parameters for rearing vannamei shrimp larvae that were measured were temperature 28-31.5°C, salinity 30-31 ppt, pH 7.7-8.1 and dissolved oxygen 5-5.7 mg/l.